The development, implementation and evaluation of a housing education literacy programme for semi-literate recipients of government subsidised housing - Venter, Maria Dorothea (Stellenbosch : University of Stellenbosch, 2006)
Thesis (PhD (Consumer Science))--University of Stellenbosch, 2006.